The effect of family doctor–contracted services on noncommunicable disease self‐management in Shanghai, China. (1st August 2019) - Huang, Jiaoling; Zhang, Tao; Wang, Luan; Guo, Dongfeng; Liu, Shanshan; Lu, Wei; Liang, Hong; Zhang, Yimin; Liu, Chengjun
Summary: Background: Noncommunicable diseases (NCDs) are a major threat to population health worldwide. In Shanghai, China, a new pattern of NCD management—self‐management—has been developed in community health service centres (CHSCs). Objective: To clarify how contracting with CHSC‐based family doctors (FDs) influences the engagement in and effectiveness of self‐management behaviour among NCD patients. Method: We conducted two waves of a questionnaire survey (in 2013 and 2016) to collect data on patients with NCDs. Separate logistic regression models and longitudinal analysis were performed to examine the effect of contracting with an FD on NCD self‐management and the effectiveness of this self‐management. Results: Nearly all contracted patients (80.79%) had implemented NCD self‐management, while only 55.57% of non‐contracted patients did so. The self‐management effectiveness rate was also higher among contracted patients than among non‐contracted ones (86.66% vs. 54.79%). In the population‐averaged models, contracted patients had 2.25 and 2.91 times greater odds of implementing self‐management and reporting that the self‐management was effective, respectively, after controlling for all related variables. Additionally, awareness of FD‐contracted services, satisfaction with CHSCs, and experiencing first contact at CHSCs had positive impacts on the implementation and effectiveness of self‐management. Conclusions: FDs were important for ensuring that NCD patients engaged in self‐management behaviour, the most common form of which was focus group. Participation in NCD focus groups may be key for attaining the effects of self‐management, including improved health knowledge, greater health awareness, more frequent engagement in health behaviour, and, most importantly, greater practice of self‐monitoring. Self‐management might help to achieve greater NCD control.